2020
DOI: 10.3390/educsci10110294
|View full text |Cite
|
Sign up to set email alerts
|

Digital Education and Artistic-Visual Learning in Flexible University Environments: Research Analysis

Abstract: The constant development of digital technologies has allowed living in a digital environment based on connections, also transforming the context of the educational process. Experiences show that digital technologies have influenced the way of learning and, consequently, the way of teaching. Learning in the digital age is a complex process since it is a multifaceted and diverse action. The aim of this research is to identify global trends in digital education and its link with the learning of artistic and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 98 publications
0
18
0
1
Order By: Relevance
“…Furthermore, Pawlowski et al (2014) pointed out that electronic devices’ availability and utilization had not previously been identified as a barrier to PA participation in children. Therefore, more research is needed to explore the impact of this relatively new barrier on PA and suggest future directions in this area [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Pawlowski et al (2014) pointed out that electronic devices’ availability and utilization had not previously been identified as a barrier to PA participation in children. Therefore, more research is needed to explore the impact of this relatively new barrier on PA and suggest future directions in this area [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that one solution was to formulate national policies to safeguard cultural values and individual rights, and finally strengthen these values in their society (Robinson 2020 ). González-Zamar et al ( 2020 ) reported that the continuous development of digital technology enabled people to live in a connection based digital environment, and also changed the background of the educational process. Besides, experience showed that digital technologies had influenced the way of learning and, consequently, the way of teaching, and learning in the digital age was a complex process because it was a multifaceted and diversified action.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors applied bibliometric techniques to identify global trends in digital education and its link with the learning of artistic and visual education in higher education settings, during the period 2000–2019, and the data showed increasing relevance, particularly in the last three years. They detected the lines of research that were related to the Internet, education, visuals, computer programs, learning, digital media literacy, and educational technology, contributing to academic, scientific, and institutional debate to enhance decision-making based on existing information (González-Zamar et al 2020 ). Leguina et al ( 2021 ) studied the interaction between cultural capital and digital capital in public libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most renowned global artists have developed websites with automatic payment systems through PayPal, Payoneer, etc., once a sale is made. With this trend of financial management, Artech was estimated to contribute 4% of the US's $800 billion year GDP in 2020 (6). This contribution was valued to be bigger than the economic output of Sweden or Switzerland.…”
Section: Artistsmentioning
confidence: 99%